La disfunción familiar en el rendimiento escolar - Guato Cando, Mónica Viviana (2017)
The investigative work presents an analysis about the family disroden and how this affects the school performance of the children of the Educational Unit “Dr. José María Velasco Ibarra”. The objective of the project is to diagnose the affectation of family disroden in the children of the educational unit. Practical usefulness, interest, novelty and feasibility are some of the factors that justify the carrying out of research work, where it is determined that the problem is subject to a study in the selected educational institution. For which the research is supported on a theoretically observed basis, where the characteristics of the difficulty in the teaching-learning process are identified, determining the most relevant aspects of the relationship with school performance, theories contributed to the Direction in the development of the project. The applied research methodology was the exploratory and descriptive with which it was determined the current situation of the problematic, through the dialectical and analytical methods established the social and psychological aspects of family disintegration and how they influence the unit Of study examined....